Direct-acting antivirals for children and adolescents with chronic hepatitis C. (April 2018) - Indolfi, Giuseppe; Serranti, Daniele; Resti, Massimo
Summary: In 2017, the US Food and Drug Administration (FDA) and European Medicines Agency (EMA) approved the fixed-dose direct-acting antiviral (DAA) combination sofosbuvir and ledipasvir and the combination sofosbuvir plus ribavirin for the treatment of adolescents (aged 12–17 years) with chronic hepatitis C. Preliminary results on the use of DAAs in paediatric patients are available for the fixed-dose combination sofosbuvir and ledipasvir in children aged 6–17 years for genotype 1 or 4 infection; for combination sofosbuvir plus ribavirin for adolescents aged 12–17 years for genotype 2 or 3 infection; for the fixed-dose combination ombitasvir, paritaprevir, and ritonavir with or without dasabuvir and with or without ribavirin for adolescents aged 12–17 years with genotype 1 or 4 infection; and for the combination of sofosbuvir plus daclatasvir for children with genotype 4 infection. All the results available indicated positive efficacy and favourable safety profiles of the different combinations of DAAs. With the approval of the new drugs, indications for treatment of children with chronic hepatitis C have changed. DAA therapy is recommended for all adolescents aged 12–17 years with chronic hepatitis C virus infection independent of treatment history and disease severity. If and when DAAs are approved for younger age cohorts, all children older than 3 years infected with hepatitis C will benefit from antiviral therapy. In this Review, we aim to provide an up-to-date overview of the existing evidence on the paediatric use of DAAs, summarising indications to treatment and recommendations for monitoring.